Qualification Of Criminal Act Of Drug Abuse With Relatively Small Amount Of Drugs Evidence - Andri Roi Saputra Manurung; Kusno Kusno; Ahamd Ansyari Siregar (CV. AFDIFAL MAJU BERKAH, 2025)
The method used in this article's research is normative legal research, namely research into problems by looking at the sources of applicable regulations relating to the title.Qualifications for Criminal Acts of Drug Abuse with Relatively Small Amounts of Narcotics Evidence. The Supreme Court as the Highest Judicial Institution has given Authority to the Panel of Judges who examine and try Narcotics cases to escape the minimum limit provisions of Article 111 or Article 112 of Law No. 35 of 2009 if indeed based on the legal facts revealed in the trial it is proven to violate the provisions of Article 127 of Law No. 35 of 2009 concerning Narcotics.; then in accordance with the provisionsArticle 127 of the Narcotics Law stipulates that: